(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The work depicts utility of a novel; surfactants based elastic vesicular drug carrier system (SEVs), for targeting topically applied drug(s) to the posterior segment of the eye. The system comprised span 20 and an edge activator (tween 80). Terbinafine hydrochloride is a synthetic allylamine antifungal with a low molecular weight (327.89 Da.). It is hydrophilic in nature and has high protein binding and a limiting solubilityis expected to show a poor transport across the cornea; hence no ocular formulations are available. It is used to treat ocular mycoses, the second most usual drive of blindness in developing countries. However, its administered poor patient compliance and limited use due to its variable half-life. Therefore, Terbinafine hydrochloride was comprised into a novel sorbitan (spans) based elastic (SEVs) vesicular system with intent to achieve a prolonged and better effect. It was found to be safe in terms of dermal and eye irritation/corrosion tests according to OECD guidelines. Safety was a crucial issue considering that the system is novel (Indian Patent Application 2390/DEL/2008; 1447/DEL/2010) and is completely surfactant based (spans plus edge activators) formulation.